2020
DOI: 10.25217/ji.v5i2.827
|View full text |Cite
|
Sign up to set email alerts
|

The SWOT Analysis of Strengthening Character Education In Junior High School

Abstract: This study aims to describe the swot analysis of character education strengthening in junior high schools which includes (1) character education curriculum management, (2) results of swot analysis of character quality improvement, and (3) the principal's strategic plan for strengthening character education based on SWOT analysis. This research was conducted at SMPN 15 Malang using a qualitative approach with a case study research design. Data was collected through in-depth interviews and documentation studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…Meanwhile, other research identifies strengths, weaknesses, opportunities, and threats in "Lifelong Learning Education Using Online Collaborative Mind-Mapping, concluding that lifelong learning requires strength" (Kamrozzaman et al, 2018). The next research identified "strengths, weaknesses, opportunities, and threats at inclusive schools in Indonesia with a SWOT analysis" (Anshory, 2018;Satria & Shahbana, 2020). In general, in previous studies with SWOT analysis to identify strengths, weaknesses, opportunities, and threats, the results obtained were not validated, and the reliability tests were carried out.…”
Section: Discussion and Suggestionmentioning
confidence: 99%
“…Meanwhile, other research identifies strengths, weaknesses, opportunities, and threats in "Lifelong Learning Education Using Online Collaborative Mind-Mapping, concluding that lifelong learning requires strength" (Kamrozzaman et al, 2018). The next research identified "strengths, weaknesses, opportunities, and threats at inclusive schools in Indonesia with a SWOT analysis" (Anshory, 2018;Satria & Shahbana, 2020). In general, in previous studies with SWOT analysis to identify strengths, weaknesses, opportunities, and threats, the results obtained were not validated, and the reliability tests were carried out.…”
Section: Discussion and Suggestionmentioning
confidence: 99%
“…The process and student learning outcomes are assessed in accordance with their social life. The steps involved in strengthening Character Education in learning include determining short and long-term programs, setting indicators, assessing performances, comparing results, linking and analyzing errors, and taking corrective actions or measures (Satria & Shahbana, 2020). According to Amran et al (2021), effectiveness, motivation, and students' learning outcomes in sports lessons are influenced by several supporting factors to achieve success.…”
Section: Character Education To Improving Student Learning Outcomesmentioning
confidence: 99%
“…Thus, it will be acknowledged, understood, and implemented in schools or society (Bates, 2019;Kosim et al, 2019;Muhamad Nova, 2017). The Presidential Regulations about PPK outlines the objectives, JERE, P-ISSN: 2597-422x E-ISSN: 2549-2675 as follows: equipping students with noble character education and spirit of Pancasila to be the golden generation in 2045, developing a national education platform upholding character education as the main spirit in administering education for students (Satria & Shahbana, 2020). Furthermore, it is conducted through formal, non-formal, and informal education by concerning the diversity of Indonesian culture, and revitalizing and strengthening potentials and competencies of teachers, education personnel, students, societies, and families in implementing PPK.…”
Section: Introductionmentioning
confidence: 99%